Characterization of material constants based on synthetic biaxial data - Roongrote Wangkiet (2018)
When applying finite element analysis (FEA) to the designing of rubber products, the material constants are required as input data. To obtain sufficiently accurate material constants, combined tests and biaxial tests are recommended. However, these tests are time-consuming and sometimes require special equipment. We propose a fast and easy method to characterize the material constants. In this method, only the tensile test is required. The tensile data are used to generate biaxial data based on the constant true Young modulus varying Poisson's ratio approach. The synthetic biaxial data are then converted into material constants by multiple regression. Compared with the material constants obtained from conventional method, those obtained from the proposed method give a better prediction of rubber behaviour under tension and simple shear modes. Even though they give a poorer prediction under compression mode, the difference between the FEA and experimental results is relatively low (∼11-12%). Thus, it could be concluded that the material constants obtained from this method could give good prediction of rubber behaviour under various types of deformation.